Carta de José Mauleón a Roberto H. Todd - Mauleón, José; Todd, Roberto H. (My University, 1942)
Carta relacionada a lápida en el Morro.
Keywords: Mauleón, José--Correspondencia.; Mauleón, José--Correspondence.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.